Rational use of fluconazole prior to attending skin & vd-opd in a tertiary Medical College Hospital in Bangladesh - Rokon Uddin; Khondaker Bulbul Sarwar; Farzana Akhter (Our Dermatology Online, 2011)
This study was done keeping the hypothesis in mind that Fluconazole is used irrationally irrespective of diagnosis. Material: All patients attending at Skin-VD OPD of Enam Medical College Hospital during a 6-month time-period (July-Dec, 2009) were considered for this research. Structured questionnaire, check-list and face-to-face interview were used as data collection tools. After careful analysis, 274 cases were found valid out of 976 respondents. The cases were mostly adult (>20 yrs., 70.4%), dominated by male (58%), marriage (54%), literacy (71.6%) and coming from far (>5 km; 65.9%). The referral was made by registered doctors (10.9%), village doctors and/or drug-sellers (50.3%) and self (38.8%). Out of the total Fluconazole-intakers (N=119), it was found that correct prescription done by registered doctors (10.08%), village doctors and/or drug sellers (9.24%) and by self (0.8%) was very few. The respondents wrongly-taken Fluconazole were finally diagnosed as case of psoriasis (21.84%), atopic dermatitis (13.44%) sebrrhoic dermatitis (12.6%) and so on. Results: The findings put this recommendation that prior to confirm diagnosis, use of Fluconazole was not rational for generalized skin lessions.